FAKTOR-FAKTOR YANG MEMPENGARUHI KEBUTUHAN INFORMASI PERTANIAN BAGI PETANI SAYURAN DI PROVINSI JAWA BARAT - Mariati Tamba; Ma‟mun Sarma (Jurnal Penyuluhan, 2007)
The agribusiness development of horticulture products is one of national economical growth sources of agricultural sector. Free market made part of domestically which cause more rigid competitiveness. In addition, the increase of farmer’s family member demands was faced to the need of demand of information of modern farming to increase the management capability in yielding competitive products from the efficient farmers. Yet, the empowerment hasn’t significantly empowered the farmers. The fact showed that farmers still lives in ’darkness’ and lack of information. One of empowerment strategy is to make independent farmer in maintaining their lives in the meaning of: knowed, motivated, and able to develop their farm by looking and using the available agricultural information. The government task is to service agricultural information for farmers as stated in law No.16 year 2006 about Agricultural Extension System. This study was aimed to analyze: (1) kinds of agricultural information which needed by vegetables’ farmers, and (2) factors influenced the need of agricultural information. The research was conducted in three districts (Bogor, Cianjur, and Bandung), West Java Province since July 2006 to February 2007 by using survey technique, interview, and indepth interview. The sampling technique used in the study was quota sampling with 240 respondents of head families. Statistical analysis were using Cronbach Alpha, t-test, Rank Spearman correlation, and Structural Equation Modeling. The analysis showed that the need of agricultural information from vegetables’ farmers’ influenced significantly by economic and social status of vegetables’ farmers, farmers’s awareness level of the importance of agricultural information, accessibility level of vegetables’farmers in obtaining the agricultural information, motivation of vegetables’ farmers ,and innovative of vegetables’ farmers.